Analysis Juridical to Legality Cryptocurrency as Investment Instruments in Indonesia: Positive Law and Islamic Law Perspectives - Sidqi, Faris Ali (Journal of Law Science, 2025)
This study presents a normative-comparative legal analysis of the legality of cryptocurrency as an investment instrument in Indonesia from both the perspectives of positive law and Islamic law. While Indonesian regulations, particularly Bappebti Regulation No. 5 of 2019, classify cryptocurrency as a tradable commodity under strict supervision, its use as a legal means of payment remains prohibited. From the Islamic legal perspective, cryptocurrency is viewed with caution due to elements of gharar (uncertainty) and maisir (speculation), although limited permissibility is recognized when Sharia principles are upheld. This study employs a statutory and conceptual approach, utilizing content analysis of legal norms and fatwas. The novelty of this research lies in its comprehensive synthesis of legal and religious frameworks, proposing a harmonized legal model that integrates ethical, spiritual, and regulatory principles. It contributes theoretically to the development of Sharia-compliant legal standards and practically to policy recommendations—such as the establishment of a Sharia screening board within licensed exchanges. By bridging the regulatory gap between secular and religious legal systems, this study provides a foundation for safer and more inclusive crypto investment policies in Indonesia's dual legal context.